The effect of excess cement on peri-implantitis: A literature review (Research, Society and Development, 2024)
Peri-implantitis (PI) is a major dental implantology challenge. Excess cement (EC) significantly impacts PI onset and progression. This review clarifies unremoved EC's effects on peri-implant tissue. A literature search from 2012 to 2024 was conducted. Eleven studies examining EC's impact on peri-implant health were included. Investigated parameters were cement type, implant diameter, EC duration, and oral microbiota-cement interaction. Studies show EC as a key PI risk, with better outcomes post-removal. Larger implant diameters correlated with higher EC risks. EC retention duration directly affected PI severity. Different cements, like methacrylate-based cement (MeC) and zinc oxide and eugenol-based cement (ZOEC), varied in affecting PI. ZOEC notably mitigated PI risks and lacked in EC cases. Early PI detection and prompt removal are crucial. Choosing ZOEC cement can significantly reduce PI risks. Dentists should use minimal cement for implant restorations. Developing standard research methods is key to validate findings and guide practice.